2021
DOI: 10.3389/fendo.2021.783670
|View full text |Cite
|
Sign up to set email alerts
|

Value of Contrast-Enhanced Ultrasound in Partially Cystic Papillary Thyroid Carcinomas

Abstract: Partially cystic papillary thyroid carcinomas (PCPTCs) are rarely reported papillary thyroid carcinomas (PTCs) and are usually misdiagnosed as benign nodules. The objective of this study was to provide the various sonographic characteristics of partially cystic thyroid nodules for differentiation between malignant and benign nodules, including those for conventional ultrasound (US) and contrast-enhanced ultrasound (CEUS). Twenty-three PCPTC patients and 37 nodular goiter patients were enrolled in this study. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Contrast-enhanced ultrasound (CEUS) could provide improved characterization of dynamic microvessel perfusion in the differential diagnosis of focal thyroid nodules compared with color Doppler US, which could help to differentiate malignant thyroid nodules from benign thyroid nodules (9,(11)(12)(13). However, MTNs with the same conventional US appearance may have different CEUS features according to our current study.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Contrast-enhanced ultrasound (CEUS) could provide improved characterization of dynamic microvessel perfusion in the differential diagnosis of focal thyroid nodules compared with color Doppler US, which could help to differentiate malignant thyroid nodules from benign thyroid nodules (9,(11)(12)(13). However, MTNs with the same conventional US appearance may have different CEUS features according to our current study.…”
Section: Introductionmentioning
confidence: 73%
“…CEUS performed technology and the ultrasound contrast agents were the same as our previous studies (9,(11)(12)(13). The CEUS videos were acquired and time-intensity curves (TICs) of the thyroid within selected regions of interest (ROIs) were analyzed according to our previous study (11).…”
Section: Ceus and Analysismentioning
confidence: 99%
“…According to the analysis of the results of ultrasound images in this study, the solid component in some cystic nodules with eccentric sharp angle, edge sharp angle, non-smooth free edge, nodule hypoechoic, or microcalcification was associated with malignant PCTNs (P<0.01). A related report found that, compared with benign nodular goiters, PCTNs more frequently presented with calcification, hypoechogenicity of the solid part, hypoenhancement, heterogeneous enhancement, centrifugal perfusion, peak intensity index <1, time to peak index ≥1, and area under the curve index <1 on preoperative US and CEUS ( 11 ). A recent review included eight studies with a total of 2,004 PCTNs.…”
Section: Discussionmentioning
confidence: 99%
“…Some malignant nodules tend to have uniform high enhancement, which may be due to the small infiltration area of cancer cells and most of the nodules are benign tissues. 51 Therefore, there are also errors in the evaluation of nodules by CEU.…”
Section: Contrast Enhanced Ultrasoundmentioning
confidence: 99%
“…Some nodules with benign pathology show uneven enhancement, which may be related to the repeated hyperplasia and degenerative changes of the lesion. Some malignant nodules tend to have uniform high enhancement, which may be due to the small infiltration area of cancer cells and most of the nodules are benign tissues 51 . Therefore, there are also errors in the evaluation of nodules by CEU.…”
Section: Contrast Enhanced Ultrasoundmentioning
confidence: 99%